(untitled) (NewYork, 2004)
Learn to design and implement a robust, scalable client/server network on Windows NT/2000, UNIX/Linux, or Novell Netware. Introduction to Client/Server Networking presents fundamental networking concepts, and teaches you how to configure a network, implement network protocols, connect workstations, plan for security, and much more. Throughout the text, you'll get hands-on tutorials, exercises, and case studies so you can apply your skills to real-world scenarios.
Keywords: Client/server computing.,Khách hàng/máy chủ tin hoc